2001
DOI: 10.2337/diabetes.50.5.1093
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Induces GLUT4 Translocation in L6 Myotubes

Abstract: A number of studies have demonstrated that insulin resistance in the skeletal muscle plays a pivotal role in the insulin resistance associated with obesity and type 2 diabetes. A decrease in GLUT4 translocation from the intracellular pool to the plasma membranes in skeletal muscles has been implicated as a possible cause of insulin resistance. Herein, we examined the effects of an insulin-sensitizing drug, troglitazone (TGZ), on glucose uptake and the translocation of GLUT4 in L6 myotubes. The prolonged exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
3
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 61 publications
(46 reference statements)
3
85
3
2
Order By: Relevance
“…Triplicate measurements of 2-deoxy-D-[1-3 H]glucose (2-DG) uptake were taken after 10 min of incubation as described [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triplicate measurements of 2-deoxy-D-[1-3 H]glucose (2-DG) uptake were taken after 10 min of incubation as described [26].…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular fractionation Membrane fractions from myotubes were prepared as described [26,27]. 5′-Nucleotidase and cytochrome c reductase activities were assayed as marker enzymes for plasma membranes and low-density microsomes, respectively [25].…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that the pathway of the signaling by troglitazone converges with that activated by insulin. We have recently demonstrated that troglitazone also increases translocation of GLUT4 in L6 myotubes (13). In L6 myotubes, it is supposed that troglitazone acts at a step beyond PI3K and PKB in which GLUT4 endocytosis is enhanced or reduces endocytosis of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study (13), inhibition of protein synthesis by cycloheximide completely eliminated the increase in translocation of GLUT4 by troglitazone in L6 myotubes. It is tempting to speculate that troglitazone affects the synthesis of some molecules involved in the translocation of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation